Integration of modeling, design and control for efficient operation of chemical processes - Abd. Hamid, Mohd. Kamaruddin; Gani, Rafiqul (DTU Chemical Engineering, 2007)
The purpose of this study is to develop a model-based methodology for integration of process design and control (IPDC) problems. The new methodology is organized in four hierarchical stages based on a decomposition of the general optimization problem. The objective of each stage is to define the search space and enumerate/test a set of promising (feasible) candidates. In each subsequent stage, the search space is reduced until in the final stage only a small number of candidates need to be evaluated. Therefore, while the problem complexity increases with every subsequent stage, the dimension and size of the problem is reduced. The proposed methodology does not have difficulties in handling complex problem formulations with large number of variables and constraints, and its applicability is highlighted in relevant case studies.